A Case of Newly Diagnosed Klippel Trenaunay Weber Syndrome Presenting with Nephrotic Syndrome. (27th April 2015) - Cebeci, Egemen; Demir, Secil; Gursu, Meltem; Sumnu, Abdullah; Yamak, Mehmet; Doner, Barıs; Karadag, Serhat; Uzun, Sami; Behlul, Ahmet; Ozkan, Oktay; Ozturk, Savas
Abstract : Klippel Trenaunay Weber syndrome (KTWS) is a rare disease characterized by hemihypertrophy, variceal enlargement of the veins, and arteriovenous (AV) malformations. Renal involvement in KTWS is not known except in rare case reports. Herein, we present a case of KTWS with nephrotic syndrome. A 52-year-old male was admitted due to dyspnea and swelling of the body for the last three months. The pathological physical findings were diffuse edema, decreased lung sounds at the right basal site, increased diameter and decreased length of the left leg compared with the right one, diffuse variceal enlargements, and a few hemangiomatous lesions on the left leg. The pathological laboratory findings were hypoalbuminemia, hyperlipidemia, increased creatinine level (1.23 mg/dL), and proteinuria (7.6 g/day). Radiographic pathological findings were cystic lesions in the liver, spleen, and kidneys, splenomegaly, AV malformation on the left posterolateral thigh, and hypertrophy of the soft tissues of the proximal left leg. He was diagnosed to have KTWS with these findings. Renal biopsy was performed to determine the cause of nephrotic syndrome. The pathologic examination was consistent with focal segmental sclerosis (FSGS). He was started on oral methylprednisolone at the dosage of 1 mg/kg and began to be followedup in the nephrology outpatient clinic.